The Influence of Accounting Understanding, Utilization of Accounting Information Systems and Implementation of Financial Accounting Standards on the Quality of Financial Reports of Pasar Segar MSMEs - Muh Agung Wirawan Safar (Mustard Journal De Ecobusin, 2024)
This research examines how accounting comprehension, accounting information system usage and use of the financial accounting standards affects the quality of financial statements in the fresh produce market. A sample size of 125 respondents who were registered in this market was used. The quantitative research design has been employed and multiple regression analysis stood as the most important analytical method. The data was collected using primary data collected by way of online questionnaires distributed to the 125 respondents who were categorized as micro, small and medium enterprises (UMKM) in the fresh produce industry. The results have shown that the understanding of accounting, the use of accounting information systems, as well as the use of financial accounting standards, has a positive and significant impact on the quality of financial statements in the fresh produce market, to a considerable degree.